Update on Superficial Spindle Cell Mesenchymal Tumors in Children - Philippe Drabent; Sylvie Fraitag (MDPI AG, 2021)
The diagnosis of cutaneous and subcutaneous spindle cell neoplasms in children is often challenging and has potential therapeutic and prognostic implications. Although correctly diagnosing dermatofibrosarcoma protuberans and infantile fibrosarcoma is paramount, pathologists should not ignore a number of diagnostic pitfalls linked to mostly rare tumors with completely different clinical outcomes. In the last decade, a spectrum of novel entities has been described; information from molecular biology has helped to shape this new landscape for spindle cell tumors. Here, we review the most noteworthy neoplasms in this spectrum, with a focus on their histological similarities: fibroblastic connective tissue nevus, medallion-like dermal dendrocyte hamartoma, or plaque-like CD34-positive dermal fibroma, which share features with fibrous hamartoma of infancy; lipofibromatosis and lipofibromatosis-like neural tumor; and plexiform myofibroblastoma, a recently described neoplasm that should be distinguished from plexiform fibrohistiocytic tumor. These tumors also have genetic similarities, particularly gene rearrangements involving NTRK3 or NTRK1. These genetic features are not only essential for the differential diagnosis of infantile fibrosarcoma but are also of diagnostic value for lipofibromatosis-like neural tumors. The more recently described RET, RAF1, and BRAF gene fusions are also discussed.